2019
DOI: 10.1037/xan0000196
|View full text |Cite
|
Sign up to set email alerts
|

Learned predictiveness models predict opposite attention biases in the inverse base-rate effect.

Abstract: Several attention-based models of associative learning are built upon the learned predictiveness principle, whereby learning is optimised by attending to the most predictive features and ignoring the least predictive features. Despite their functional similarity, these models differ in their formal mechanisms, and thus may produce very different predictions in some circumstances. As we demonstrate, this is particularly evident in the inverse base-rate effect. Using simulations with a modified Mackintosh model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 72 publications
5
41
2
Order By: Relevance
“…Patterns of gaze biases support the idea that greater relative attention is paid to Cue C on AC trials than to Cue B on AB trials, under typical base-rate designs (e.g., the inverse base-rate effect: Don et al, 2019; and the highlighting effect 2 : Kruschke et al, 2005). Don et al (2019) measured gaze biases to cues both prior to making a prediction and during feedback, and assessed how gaze patterns differed based on the global base rates of the outcomes. Manipulation of the global base rates should affect the associations between the context and the prevailing common outcomes, where the context comprises the incidental cues related to features of the experimental trials and participating in the experiment more generally.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…Patterns of gaze biases support the idea that greater relative attention is paid to Cue C on AC trials than to Cue B on AB trials, under typical base-rate designs (e.g., the inverse base-rate effect: Don et al, 2019; and the highlighting effect 2 : Kruschke et al, 2005). Don et al (2019) measured gaze biases to cues both prior to making a prediction and during feedback, and assessed how gaze patterns differed based on the global base rates of the outcomes. Manipulation of the global base rates should affect the associations between the context and the prevailing common outcomes, where the context comprises the incidental cues related to features of the experimental trials and participating in the experiment more generally.…”
supporting
confidence: 56%
“…This account has been formalised in Kruschke’s (2001b) extended ADIT (EXIT) model, which is based on learned predictiveness principles like those proposed by Mackintosh (1975). Yet, the EXIT model and variants of Mackintosh’s model have been shown to make different predictions regarding attention to cues in the inverse base-rate effect (Don et al, 2019). Although EXIT is a relatively complex model containing several mechanisms, Paskewitz and Jones (2020) have shown that the EXIT model only requires rapid attentional shifts or attentional competition components to explain most experimental effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, participants are asked to judge which foods are causing Mr. X to suffer an allergic reaction, and this judgment may also take the form of a probability or cued recall judgment. The food allergist task has been used to study cue competition effects such as blocking and overshadowing (e.g., Shanks and Lopez, 1996 ; Aitken et al, 2000 ; Lovibond et al, 2003 ; Beckers et al, 2005a ; Mitchell et al, 2005 , 2006 ; Vandorpe et al, 2007 ; Livesey et al, 2013 , 2019b ; Luque et al, 2013 ; Uengoer et al, 2013 ), learning of preventative relationships such as in the case of conditioned inhibition ( Karazinov and Boakes, 2004 , 2007 ), complex rule learning tasks such as the patterning task ( Shanks and Darby, 1998 ; Wills et al, 2011 ; Don et al, 2020 ), as well as a host of phenomena related to learned attentional changes including the learned predictiveness effect ( Le Pelley and McLaren, 2003 ; Don and Livesey, 2015 ; Shone et al, 2015 ), the inverse base-rate effect ( Don et al, 2019 ), outcome predictability effects ( Griffiths et al, 2015 ; Thorwart et al, 2017 ), and other related transfer effects ( Livesey et al, 2019a ). Food allergies are relatively commonplace such that, by the time they enter the laboratory, participants have a lifetime of experience with food and its ability to cause allergic reactions in oneself or others.…”
Section: Introductionmentioning
confidence: 99%